EXPLORING EFL STUDENT’S DESCRIPTIVE TEXT BASED ON SYSTEMIC FUNCTIONAL LINGUISTICS: A CASE STUDY AT SMAN 1 KARTASURA - Fiscarina, Canna Vionitaretami; Fauziati , Endang (Jurnal Review Pendidikan dan Pengajaran, 2024)
The purpose of this study was to identify descriptive texts written by students using the framework systemic functional linguistics. The researchers looked at three aspects, (1) generic structure, (2) linguistic features focusing on type of process within transitivity system, and (3) communicative purposes. The subjects of this study were 50 students at SMAN 1 Kartasura class XI. This study is a descriptive qualitative with a case study approach. The data were students’ descriptive text, collected by elicitation techniques namely the results of students' descriptive text. The result of the study showed students are able to apply the appropriate generic structure of the descriptive text namely identification and description. Moreover, in terms of linguistic features, the most dominant process is relational process. Further, the communicative purpose of the descriptive texts written by students such as their favourite electronics and hobbies represents the students’ daily favourite things and preference. This study can give benefits for help teachers to find out students' ability to write descriptive text using the SFL perspective based on the generic structure, linguistic features, and communicative purpose. Moreover, helps the students in learning, especially in descriptive text material.